PENGARUH BI RATE DAN FED RATE TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2019 - Pandu Adijaya, - (2021)
This study aims to analyze and determine the effect of the BI Rate and Fed Rate on Indonesia Composite Index on the Indonesia Stock Exchange in the period of 2015-2019 simultaneously and partially. The research uses descriptive and verification methods. The data used in this study is secondary data sourced from the company's website. The sampling technique used the purposive sampling method. The data analysis model used is the classical assumption test and multiple linear regression analysis. EViews 10 was used for data processing. Based on the F test, BI Rate and Fed Rate have an effect on Indonesia Composite Index simultaneously. Based on the t-test, BI Rate does not have an effect on Indonesia Composite Index, while the Fed Rate has a positive and significant effect on Indonesia Composite Index.